Preserved Ratio Impaired Spirometry in US Primary Care Patients Diagnosed with Chronic Obstructive Pulmonary Disease - Evans A; Tarabichi Y; Pace WD; Make B; Bushell N; Carter V; Chang KL; Fox C; Han MK; Kaplan A; Kocks JWH; Le Lievre C; et al. (Pragmatic and Observational Research)
Alexander Evans,1 Yasir Tarabichi,2 Wilson D Pace,3,4 Barry Make,5 Nicholas Bushell,6 Victoria Carter,7 Ku-Lang Chang,8 Chester Fox,9 MeiLan K Han,10 Alan Kaplan,11,12 Janwillem WH Kocks,13– 15 Chantal Le Lievre,6 Alexander Roussos,6 Neil Skolnik,10,16 Joan B Soriano,17 Barbara P Yawn,10 David Price1,6,7,18 1Observational and Pragmatic Research Institute, Singapore, Singapore; 2Center for Clinical Informatics Research and Education, MetroHealth, Cleveland, OH, USA; 3DARTNet Institute, Aurora, CO, USA; 4Department of Family Medicine, Anschutz Medical Campus University of Colorado, Aurora, CO, USA; 5Department of Medicine, National Jewish Hospital, Denver, CO, USA; 6Optimum Patient Care, Brisbane, Queensland, Australia; 7Optimum Patient Care, Oakington, Cambridge, UK; 8Lucas Research, a Centricity Research Company, Morehead City, NC, USA; 9University at Buffalo, Buffalo, NY, USA; 10University of Minnesota, Minneapolis, MN, USA; 11Family Physician Airways Group of Canada, Stouffville, Ontario, Canada; 12University of Toronto, Toronto, Canada; 13General Practitioners Research Institute, Groningen, the Netherlands; 14Groningen Research Institute Asthma and COPD (GRIAC), University of Groningen, University Medical Center Groningen, Groningen, the Netherlands; 15Department of Pulmonology, University of Groningen, University Medical Center Groningen, Groningen, the Netherlands; 16Abington Jefferson Health, Jenkintown, PA, USA; 17School of Medicine, Universitat de les Illes Balears, Palma, Spain; 18Centre of Academic Primary Care, Division of Applied Health Sciences, University of Aberdeen, Aberdeen, UKCorrespondence: David Price, Observational and Pragmatic Research Institute, 22 Sin Ming Lane, #06-76, Midview City, Singapore, 573969, Singapore, Tel +65 3105 1489, Email dprice@opri.sgBackground: Preserved ratio impaired spirometry (PRISm) represents a population with spirometry results that do not meet standardized COPD obstruction criteria, yet present with high respiratory symptom burden and might benefit from respiratory management and treatment. We aimed to determine prevalence of PRISm in US primary care patients diagnosed with COPD, describe their demographic, clinical, and CT scan characteristics.Methods: An observational registry study utilizing the US APEX COPD registry, composed of patients diagnosed with COPD aged 35+ years. Demographic and clinical data were collected from EHRs and complemented by questionnaires. Multivariable logistic regression was performed to assess whether PRISm predicts lung function decline.Results: Prevalence of PRISm within a primary care population clinically diagnosed with COPD was 23.6% (678/2866, 95% CI 22.0– 25.1). Those with PRISm were more likely female (55.9% vs 46.9%), younger (66.3± 11.1 vs 69.2± 10.3 years), with a greater mean BMI (33.5± 9.2 vs 27.8± 7.2 kg/m2), more often African American or Hispanic (37.2% vs 26.3%), and with fewer current smokers (33.1% vs 36.8%) when compared to those meeting COPD spirometry criteria (all p< 0.05). Compared to COPD GOLD 0 patients, individuals with PRISm had greater BMI (33.5± 9.2 vs 30.6± 7.8), and were more likely current smokers (33.1% vs 23.4%), both p< 0.05. Patients with PRISm had similar respiratory symptoms (chronic bronchitis, CAT, and mMRC) to overall COPD patients, but more frequently than GOLD 0 COPD patients (p< 0.01). Emphysema was more commonly reported in CT scans from patients with PRISm 70.3% (260/369, 95% CI 65.8– 75.3) than those with GOLD 0 COPD 64.1% (218/340, 95% CI 58.8– 69.2) (p< 0.05). PRISm status was not predictive of lung function decline.Interpretation: One in four primary care patients with clinically diagnosed COPD in a large US registry fulfil the spirometric definition of PRISm rather than COPD, but suffers from emphysema in CT and significant respiratory symptoms.Keywords: APEX, COPD, PRISm, US primary care, COPD exacerbations, electronic health records, patient reported outcomes